The effect of measuring the level of application of the elements of the integrated report on the disclosure in the financial reports of Iraqi government units / University of Baghdad (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to shed light on the concept and importance of integrated business reports, guidelines and elements of their informational content, as well as accounting disclosure in government units. The research community was represented by non-profit government units, while the research sample was chosen by the University of Baghdad as an intentional sample for the research. To achieve the goal of the research, the researchers prepared a survey form to measure the level of application of financial and non-financial indicators in the governmental unit (University of Baghdad) in the form of percentages according to the elements of the integrated report according to the (IR) version in 2021, with the use of indicators of the Global Reporting Initiative (GRI) according to its latest version In 2020 with its economic, social and environmental dimensions on the elements of the integrated report, and based on the financial and non-financial reports issued by University of Baghdad for the year 2019,The most prominent finding of the research is that the percentage level of disclosure according to the international framework for the integrated report (IR) for the governmental unit / University of Baghdad was (38%), which is a weak percentage of disclosure compared to (100%), and the researchers recommended the need for the governmental unit to adopt the International Integrated Reporting Framework ( IR ) because it provides a detailed and comprehensive presentation of all financial and non - financial information in a transparent and credible manner.